Influence of Dead Cells Killed by Industrial Biocides (BAC and DBNPA) on Biofilm Formation - Ana C. Barros; Diogo A. C. Narciso; Luis F. Melo; Ana Pereira (MDPI AG, 2024)
Industrial biocides aim to keep water systems microbiologically controlled and to minimize biofouling. However, the resulting dead cells are usually not removed from the water streams and can influence the growth of the remaining live cells in planktonic and sessile states. This study aims to understand the effect of dead Pseudomonas fluorescens cells killed by industrial biocides-benzalkonium chloride (BAC) and 2,2-dibromo-3-nitrilopropionamide (DBNPA)-on biofilm formation. Additionally, the effect of different dead/live cell ratios (50.00% and 99.99%) was studied. The inoculum was recirculated in a Parallel Plate Flow Cell (PPFC). The overall results indicate that dead cells greatly affect biofilm properties. Inoculum with DBNPA-dead cells led to more active (higher ATP content and metabolic activity) and thicker biofilm layers in comparison to BAC-dead cells, which seems to be linked to the mechanism of action by which the cells were killed. Furthermore, higher dead cell ratios (99.99%) in the inoculum led to more active (higher culturability, metabolic activity and ATP content) and cohesive/compact and uniformly distributed biofilms in comparison with the 50.00% dead cell ratio. The design of future disinfection strategies must consider the contribution of dead cells to the biofilm build-up, as they might negatively affect water system operations.